A Study on the Use of Speech Acts: A Review of Selected Paper - Sari Gowasa, Nofita; Permata Radiana, Sonia; Afifah, Nur (Elsya : Journal of English Language Studies, 2019)
This article is a review of the theory of speech act by Searle & Austin (1962). Describe what the action strategies used in the language themselves are speaking and what speech acts are used by a group of prospective teachers while apologizing, complaining, rejecting and giving thanks. Focusing on the paper written by Akdeniz University, Faculty of Education Nihat Bayat, titled ‘A study on the use of speech acts.’ This present paper uses descriptive qualitative analysis in an attempt to address the gap how to determine what type of speech act is used in the Turkish language strategy, which will provide convenience in teaching Turkish as a native and foreign language. Look at using data content analysis obtained from descriptive analysis for deeper processes. The data in this study were collected through asking participants to write the structure of the language they used in apologizing, complaining, rejecting and thanking. This present article aims to review and discuss the findings, as well as the strengths and weaknesses found in Nihat's paper. The article seems to have a clear flow on how to explain these two types of education and made the discourse easy to understand. Therefore, the replication of Nihat's research should be easy enough for similar research purposes.